The needs of special prison for Syariah offenders in Malaysia / Alizah Ali ... [et al.] - Ali, Alizah; Shaari, Nurulhasni; Ismail, Noraini; Abu Bakar, Zarikh Sofiah (UiTM Cawangan Johor, 2018)
Population density among the prison community has been a debating issue in Malaysia. This is might due to the placement of both civil and syariah offenders in one place. It should be highlighted that, the placement of syariah and civil offenders in the same cell could be the root of many problems. Therefore, this study is directed to discuss the needs of separating the placement of the civil and syariah offenders. In the effort of separating these two types of offenders, several aspects need to be pondered upon, which are the policies, objectives, implementations, modules and training faced by them. Other than that, the separation is important in upholding justice, as well as achieving the punishment objectives. This conceptual study involves books, articles, journals and previous literature. Based on the findings, there are a lot of differences between the punishments for civil and syariah offenders, even though they share the same punishment objectives, which are to give them lesson. By referring to differences established, this study strongly agreed on promoting the needs of special prison for syariah offenders.